Design learning in mathematics education: Engaging early childhood students in geometrical activities to enhance geometry and spatial reasoning - Novita, R; Putra, M; Rosayanti, E; Fitriati, F (Journal of Physics: Conference Series, 2018)
Understanding geometry and spatial reasoning is an essential area of mathematics learning. Besides, geometry and spatial reasoning serve as the foundation for most learning of mathematics and other subjects, especially for early childhood students. Unfortunately, these aspects are often ignored or minimized in early education and the professional development of early childhood teachers. This case may be due to a lack of activities which involve students to reason about geometric phenomena in their surrounding world. Therefore, this study aimed to design an instructional activity to guide the early childhood students in understanding geometry and spatial reasoning by doing some activities related to shapes. Therefore, this study used van den Akker et al. design research model including three phases, namely: Preparing for the experiment, Experiment in the classroom, and Retrospective analysis. The study involved 13 children ages 4-5 in one of the kindergartens in Banda Aceh, Indonesia. Teaching experiment results showed that the learning trajectory developed is potential to make a significant difference in the geometry learning of early childhood helps children to connect their experience about various types of form in their life with mathematical knowledge (i.e., geometry and spatial reasoning) that allows them to reinvent and reinforce the geometry concept.